2017
DOI: 10.1063/1.4979645
|View full text |Cite
|
Sign up to set email alerts
|

Platinum composite nanowires for ultrasensitive mass detection

Abstract: Platinum (Pt) composite nanowires were grown on the tip of tungsten (W) microprobes by focused-electron-beam induced chemical vapor deposition (FEB-CVD). An electrical field was used to drive a transversal mechanical vibration of the nanowires. Such nanowire vibrations were found to display the first and second harmonic resonances with frequencies in the range of tens of MHz. The Young's modulus of the nanowires was estimated to be in the range of (1.4 ± 0.1) × 102 GPa to (4.7 ± 0.2) × 102 GPa, dependent on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…[35] No scrolling can be attributed to the high stiffness of single-layer MoS 2 . [37][38][39] In addition, all of the decoupled MoS 2 -shells turned into monolayer MoS 2 nanobelts upon the removal of PMMA by using acetone solution ( Figure S1a, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[35] No scrolling can be attributed to the high stiffness of single-layer MoS 2 . [37][38][39] In addition, all of the decoupled MoS 2 -shells turned into monolayer MoS 2 nanobelts upon the removal of PMMA by using acetone solution ( Figure S1a, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Close to resonance, the pillar starts vibrating with a visible amplitude, which is reflected by a Gaussian peak in the amplitude versus frequency diagram (top). Alternatively, the excitation can be applied via electrostatic forces by using an electrode as was performed in the experiments shown in Figure 9a-g. Hao et al [90] were able to excite also the second harmonic frequency f 2 (the pre-factor becomes (4.69409) 2 in Equation (14) in their FEBID pillars, as shown in Figure 9c. A peculiar feature of their experiment was that the pillar had a very non-uniform base part with large diameter variations (leading to non-uniform mass distribution), which probably explains their observation that the first fundamental vibration mode was excited at multiple frequencies (at 0.5 f 1 , f 1 , and at 2 f 1 in our notation).…”
Section: Density Of Febid and Fibid Nanostructuresmentioning
confidence: 99%
“…By monitoring the current through these bridges, the mechanical resonance (see Figure 9e,f) could be read out externally, which allowed the detection of surface adsorbed molecules down to (sub-)monolayer coverages. [47] For completion, Igaki et al showed that the mass sensitivity of their high-aspect carbon FIBID pillar reached the 10 femtogram range [86], and Hao et al [90] demonstrated the mass sensitivity of their Pt-C FEBID pillar to be 0.4 attograms.…”
Section: Density Of Febid and Fibid Nanostructuresmentioning
confidence: 99%
See 2 more Smart Citations